2007
DOI: 10.1002/da.20224
|View full text |Cite
|
Sign up to set email alerts
|

Future orientation moderates the relationship between functional status and suicide ideation in depressed adults

Abstract: Functional impairment might amplify suicide risk in later life. A positive view of the future may reduce this risk. We tested the hypothesis that hopelessness and positive future orientation moderate the association between functional status and suicide ideation in a sample of 136 patients, 55 years of age or older, in treatment for depression. Future orientation moderated the association between functional status and suicide ideation; hopelessness did not. Although prospective research is needed to test more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 60 publications
3
51
0
Order By: Relevance
“…We chose hopelessness and optimism as key outcome measures due to their established links to suicidality [10][11][12]. Hopelessness has been associated with completed suicide, independent of severity of mood symptoms [46,47], and therefore we chose hopelessness rather than depression as our primary negative psychological measure, especially given the transdiagnostic nature of our study cohort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose hopelessness and optimism as key outcome measures due to their established links to suicidality [10][11][12]. Hopelessness has been associated with completed suicide, independent of severity of mood symptoms [46,47], and therefore we chose hopelessness rather than depression as our primary negative psychological measure, especially given the transdiagnostic nature of our study cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Optimism, gratitude and other positive states have been associated with reductions in hopelessness, suicidal ideation and suicide attempts, often independent of depression [10][11][12][13][14][15][16]. Positive emotions in suicidal patients have been linked to improved problem-solving [17], and a study of patients hospitalized for self-harm found that low positive future orientation more strongly predicted recurrent selfharm after discharge than did global hopelessness [18].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, individuals experiencing difficult life circumstances may be unable to positively reframe or reappraise their negative life experiences (Carver, Scheier, & Weintraub, 1989;Folkman, 1997), an ability that has been found to influence successful reduction of stress-related symptoms (Hirsch et al, 2007b). Further, individuals with a tendency to view the world in a future-oriented manner may think about negative and potentially traumatic life circumstances more favorably and may be less likely to think about or attempt suicide (Hirsch et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Strong psychometric support exists for the scale in clinical samples (Chang et al, 2013;Hirsch et al, 2007). In the present sample, Cronbach's alpha was .87.…”
Section: Methodsmentioning
confidence: 50%